Rationale for Imaging Referral Guidelines in Rectal Cancer Patients - Gupta, Sanchita; Goyal, Ankur; Sharma, Raju (Journal of Gastrointestinal and Abdominal Radiology, 2025)
Rectal carcinoma is an important cause of cancer-related morbidity and mortality worldwide, with an increasing incidence among young patients. Rectal cancers differ anatomically from other colonic cancers due to their proximity to critical pelvic structures like the anal sphincters and urinary bladder. Advances in surgical techniques (total mesorectal excision) and the introduction of neoadjuvant chemoradiotherapy have improved survival, reduced recurrence, and significantly reduced postoperative incontinence in these patients.Imaging is crucial for preoperative staging and prognostication, defining surgical planes, planning and assessing response to neoadjuvant therapy, and long-term surveillance. High-resolution pelvic magnetic resonance is considered the workhorse for evaluating rectal carcinoma malignancies. As a result, the radiologist is a vital part of the multidisciplinary team comprising surgeons, gastroenterologists, medical and radiation oncologists, and pathologists in managing rectal cancer.This review aims to provide a comprehensive insight into the imaging recommendations for rectal cancer evaluation at different time points of the management algorithm of rectal carcinoma and the rationale behind them.
Keywords: rectal cancer; MRI; neoadjuvant chemotherapy; guidelines